ANALISIS KAJIAN KEMUNDURAN DAN KERUNTUHAN DINASTI FATHIMIYAH (SEBUAH STUDI PUSTAKA) - Dalimunthe, Latifa Annum (NALAR, 2017)
The Fathimiyah caliphate, one of the Ismaili Shi'ite Islamic dynasties, in 909 AD in North Africa after defeating the Aghlabiah Dynasty in Sijilmasa. In history, the glory of Fathimiyah dynasty includes the system of government, philosophy, science and literature. After the reign of the caliph Al-Aziz Fathimiyah dynasty began to decline until the collapse. Problem formulation: How the formation of Fathimiyah dynasty. How to advance the civilization of the Fathimiyah Dynasty? How the decline and collapse of the Fathimiyah dynasty.Research Methodology: The research process is done by taking literature study from literarure, books. To discuss the results of research done by linking descriptions of literature, and books.The results show that: The founder of the Fathimiyah Dynasty was Sa'id ibn Husayn. At the end of the 9th century AD, Abu Abdullah al-Husayn al-Shi'i, one of the main propagandists of the Shiite leader of Isma'iliah, was from Yemen son of the Berber tribe in North Africa, as the main envoy of Imam Mahdi and managed to influence the Berber community. Ziyadatullah al-Aghlabi 903-909 M (Aghlabiah dynasty) is in power in North Africa centered in Sijilmasa. Having succeeded in establishing his influence in North Africa, Abu Abdullah Al-Husain wrote a letter to the Ismaili Imam, Sa'id bin Husain As-Salamiyah to leave immediately for Utar Africa. In 909 AD Sa'id proclaimed himself a priest with the title Ubaidullah Al-Mahdi. In history, the glory of Fathimiyah dynasty includes the system of government, philosophy, social conditions, scholarship and literature. The decline and disintegration of the Fathimiyah Dynasty, the caliph Fathimiyah initially controlled all activities, but among the caliphs there were those who handed the supervisory duties to the amir, because the age of the caliph was underage and did not even understand the political world. For example, after Al-Aziz died, Abu Ali Al-Mansur was eleven years old appointed to replace him with the title of Al-Hakim. The final period of the Fathimiyah Dynasty rivalry for the post of prime minister is increasingly widespread, such as Syawar with Dhargam. End of Nuruddin Mahmud's entry to help him reclaim his power from the hands of Dhargam. Al-Adhid, the last Fathimiyah caliph passed away 10 Muharram 567 H / 1171 M. then the Fatimid dynasty was destroyed after reigning for about 280 years, then Saladin holds the Caliphate.Keywords: dynasty, fathimiyah